If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -28 = 5(1 + -6x) Reorder the terms: -28 + 3x = 5(1 + -6x) -28 + 3x = (1 * 5 + -6x * 5) -28 + 3x = (5 + -30x) Solving -28 + 3x = 5 + -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. -28 + 3x + 30x = 5 + -30x + 30x Combine like terms: 3x + 30x = 33x -28 + 33x = 5 + -30x + 30x Combine like terms: -30x + 30x = 0 -28 + 33x = 5 + 0 -28 + 33x = 5 Add '28' to each side of the equation. -28 + 28 + 33x = 5 + 28 Combine like terms: -28 + 28 = 0 0 + 33x = 5 + 28 33x = 5 + 28 Combine like terms: 5 + 28 = 33 33x = 33 Divide each side by '33'. x = 1 Simplifying x = 1
| 3(y-6)+5y=6 | | 4x+12=1x-6 | | -3(2z-8)-2(z-8)-9z= | | 4b+18=-12b | | -6+3y=2y+4 | | 3k*5=2*3k | | K+32=28 | | -6x-2(x+2)=2(1-5x) | | -33=3(u+3)+3u | | 15-5x+15+2+1=2x-2+10+2 | | 3x^2+1x+6=0 | | -15+n=-0 | | 23y+90+4(10.25-0.125y)+4=180 | | X+15=25+12 | | -3(x+5)-3x=5-(2+x)+7 | | 142=7+3(-7x+3) | | g-1.6=2.8 | | .8*X=24 | | 14+12v=-16+9 | | 20-43=3(x-1)-5 | | 0=6x+13 | | j-3.79=14.21 | | 21y-1=4x+23+9x-38 | | y=6(0)+13 | | 80*X=24 | | x+2x+(x+3)=75 | | 11b-12=-10 | | f+6=8 | | 6(5)-1=5(5-1)-3(7-2(1)) | | 5=q+2 | | 9(0)-7y=14 | | 10x-3=20+15 |